Higher radiation dose on immune cells is associated with radiation-induced lymphopenia and worse prognosis in patients with locally advanced esophageal squamous cell carcinoma - Qiu, Jianjian; Lin, Hancui; Ke, Dongmei; Yu, Yilin; Xu, Jiaying; Qiu, Hejin; Zheng, Qunhao; Li, Hui; Zheng, Hongying; Liu, Lingyun; Wang, Zhiping; Yao, Qiwei; et al. (Frontiers in Immunology, 2023)
Background: To explore the effective dose to immune cells (EDIC) for better prognosis while avoiding radiation-induced lymphopenia (RIL) in patients with locally advanced esophageal squamous cell carcinoma (ESCC). Methods and materials: Overall, 381 patients with locally advanced ESCC receiving definitive radiotherapy with or without chemotherapy (dRT ± CT) between 2014 and 2020 were included in this study. The EDIC model was calculated by radiation fraction number and mean doses to the heart, lung, and integral body. The correlation between EDIC and clinical outcomes was analyzed using Cox proportional hazards regression, and risk factors for RIL were determined by logistic regression analysis. Results: The median EDIC was 4.38 Gy. Multivariate analysis revealed that low-EDIC significantly improved the OS of patients when compared with high-EDIC (HR = 1.614, P = 0.003) and PFS (HR = 1.401, P = 0.022). Moreover, high-EDIC was associated with a higher incidence of grade 4 RIL (OR = 2.053, P = 0.007) than low-EDIC. In addition, we identified body mass index (BMI), tumor thickness, and nodal stage as independent prognostic factors of OS and PFS, while BMI (OR = 0.576, P = 0.046) and weight loss (OR = 2.214, P = 0.005) as independent risk factors of grade 4 RIL. In subgroup analyses, the good group had better clinical outcomes than the remaining two groups (P < 0.001). Conclusion: This study demonstrated that EDIC significantly correlates with poor clinical outcomes and severe RIL. Optimizing treatment plans to decrease the radiation doses to immune cells is critical for improving the outcomes.